Etnomatematika Cagar Budaya Rumah Kampung Kapitan Dan Pengintegrasiannya Dalam Pembelajaran Matematika SMP - Efryanty; Somakim; Budi Mulyono (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2023)
The aims of this research are: 1) To describe the results of ethnomathematics exploration in the form of philosophical meaning contained in design; 2) Produce ethnomathematics-based LKPD on the cultural heritage of Kapitan Village houses in Palembang that is valid and practical; 3) Measuring the potential effect of ethnomathematics-based LKPD on junior high school mathematics learning outcomes. This research uses ethnographic research methods to describe the results of ethnomathematics exploration in the form of philosophical meaning contained in the design of the houses of Kampung Kapitan Palembang. Furthermore, the results of the ethnomathematics exploration of the Kapitan Village House Cultural Heritage will be made into teaching materials in the form of ethnomathematics-based LKPD. At this stage the type of research used is design research with the type of development studies. This research produces a philosophical meaning that is contained in the Kapitan Village House Cultural Heritage, especially in rectangular shapes (rectangles, rhombuses and trapezoids. After being integrated into ethnomathematics-based LKPD, it shows that 84% of students who have completed mathematics learning are in the effective category. Keywords: Ethnomathematics, Cultural Heritage, Kapitan Village, LKPD